The Cost of Stability: Consumption‐Based Fixed Rate Billing for Water Utilities. (April 2017) - Schmidt, Amy; Lewis, Lynne
Abstract: Municipal water utilities in the United States face the challenge of balancing the potentially conflicting goals of sending signals about water scarcity and maintaining revenue stability. Times of extreme shortage such as the current extended drought in California seriously challenge and can jeopardize this delicate balance. Mandatory or voluntary conservation strategies can be detrimental to revenue stability. This study explores the ability of the Consumption‐Based Fixed Rates (CBFR) pricing method to solve this dual dilemma of scarcity pricing and revenue stability in both normal times and times of drought. CBFR proposes using a proportional consumer pricing system directly based on utility supply costs. We utilize utility‐side cost data from Lomita, CA and Longmont, CO, to estimate how consumer prices change under the CBFR method. Using simulations comparing current pricing mechanisms with the CBFR, we find that the latter solves the revenue problem, but creates greater problems with equity and scarcity versus the former. A modified structure of CBFR, with prices based partially on household income, seems to alleviate some of these problems and could prove to be a useful tool during times of drought.